BUSINESS CYCLE IN THE INDUSTRIAL PRODUCTION OF BRAZILIAN STATES - Portugal, Marcelo (2009)
The present paper applies the Markov switching model with the aim of checking two industrial production features of six major Brazilian states. Firstly, we try to determine the date of business cycles and, soon afterwards, we verify the existence or not of an unobservable component that is common to all series from 1980 to 2001. The characteristics of this comovement are checked by multivariate models. The results from the univariate estimates allow us to infer about the existence of a similar behavior between the industrial production of the southeastern states and that observed in the southern states. The multivariate model efficiently captures the cyclic behavior of industrial production when used regionally, thus revealing a dynamics for growth and recession periods, which differs between these two regions.